A cross‐sectional serum investigation of a clustering hepatitis C virus infection in Southwest China. Issue 3 (9th October 2018) - Peng, Haoran; Zhang, Longyan; Feng, Yue; Tang, Hailin; Luo, Zhenghan; Qi, Zhongtian; Xia, Xueshan; Zhao, Ping
Abstract : Serum samples were collected in a village with a clustering hepatitis C virus (HCV) infection. HCV antibody, HCV RNA loads, liver function indexes, HCV envelope antibody, and neutralizing activity were assessed. Among 851 adult sera, 342 samples were positive for anti‐HCV. Of these positive samples, 254 (74.3%) were HCV RNA positive (≥800 copies/mL). None of the 69 children's sera were positive for HCV antibody or RNA. Among the HCV antibody positive sera, alanine aminotransferase, and aspartate aminotransferase levels increased with the higher virus loads, but decreased when virus loads were higher than 1 × 10 6  copies/mL. HCV envelope antibody and neutralizing antibody levels increased with viral load.